Odpowiedzi

Najlepsza Odpowiedź!
2010-01-27T16:13:35+01:00
A) (x-2)-(2-x)
x-2-2+x
2x-4

b) (a+b)+(2a-b)-(a-2b)
a+b+2a-b-a+2b
2a+2b

c) (3x-y+1)-(x+y)+(y-x)
3x-y+1-x-y+y-x
x-y+1
d) -(2a do kwadratu -3ab)-(2b-3a do kwadratu)+(-ab-b)
-2a²+3ab-2b+3a²-ab-b
a²+2ab-3b
2010-01-27T16:14:21+01:00
A) (x-2)-(2-x) = x-2-2+x=2x-4
b) (a+b)+(2a-b)-(a-2b) = a+b+2a-b-a+2b=2a+2b
c) (3x-y+1)-(x+y)+(y-x) =3x-y+1-x-y+y-x=x-y+1
d) -(2a do kwadratu -3ab)-(2b-3a do kwadratu)+(-ab-b) =-2a²+3ab-2b+3a²-ab-b=a²+3ab+b
2010-01-27T16:15:31+01:00
A). x-2-2+2=x-2
b). a+b +2a - b -a +2b = 2a + 2b
c). 3x-y+1-x-y+y-x= x - 1y +1
d) - 2a³-3ab-2b+3a²+ (-ab) - b